2009
DOI: 10.1007/s10957-009-9572-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenomena in Inverse Stackelberg Games, Part 2: Dynamic Problems

Abstract: Dynamic two-person games are considered, in which the roles of the players are hierarchical. One player behaves as a leader, the other one as a follower. Such games are named after Stackelberg. In the current paper, a special type of such games is considered, known in the literature as inverse Stackelberg games. In such games, the leader announces his strategy as a mapping from the follower's decision space into his own decision space. Arguments for studying such problems are given. This paper specifically stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…We have recently introduced ( [16], [17]) the optimal toll design problem, in which the link tolls are computed as functions of link or route traffic flows in the network. This fits within the theoretical framework of the so-called inverse Stackelberg problems ([18], [19]). We have shown that the traffic-flow dependent toll can improve the traffic system performance remarkably, while it can never perform worse than the trafficflow invariant toll.…”
Section: Introduction and Literature Overviewsupporting
confidence: 67%
“…We have recently introduced ( [16], [17]) the optimal toll design problem, in which the link tolls are computed as functions of link or route traffic flows in the network. This fits within the theoretical framework of the so-called inverse Stackelberg problems ([18], [19]). We have shown that the traffic-flow dependent toll can improve the traffic system performance remarkably, while it can never perform worse than the trafficflow invariant toll.…”
Section: Introduction and Literature Overviewsupporting
confidence: 67%
“…For both players, it concerns a one-shot game. In the subsequent paper [14], dynamic inverse Stackelberg problems will be considered; time evolution plays an essential role in the sense that both players act more than once.…”
Section: Example 14mentioning
confidence: 99%
“…the so-called inverse Stackelberg equilibrium, where the leader does not announce his action u L , but his reaction function γ L (u F ). This concept can be used to enforce a by the leader desired behavior of the follower (see [52], [53]). Closely related to this are games of mechanism design for, so-called, Bayesian games (i.e.…”
Section: Choice Of Actionsmentioning
confidence: 99%